2010
DOI: 10.1182/blood.v116.21.3492.3492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glutathione S-Transferase A1 and P1 Polymorphisms on the Outcome of Hematopoietic Stem Cell Transplantation with Busulfan Based Conditioning Regimen In Children.

Abstract: 3492 Introduction: Busulfan has narrow therapeutic range. High exposure is associated with systemic toxicity such as veno-occlusive disease (VOD) while underexposure results in graft failure or relapse. In children, pharmacokinetic variability was found to be high even after the introduction of intravenous busulfan. Busulfan is metabolized via liver through conjugation with glutathione S-transferase (GST) family, and inter-individual variability may be explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In our population, we found that GSTA1 A-513G heterozygous (AG) had a higher incidence of graft loss than the wild-type (AA) (40% versus 8%; P = 0.006). A study by Lee et al 25 found that the GSTP1 A313G mutant homozygous (AA) allele was associated with increased risk of graft loss ( P = 0.01). Low Bu exposure is thought to be the most common factor influencing graft loss.…”
Section: Discussionmentioning
confidence: 99%
“…In our population, we found that GSTA1 A-513G heterozygous (AG) had a higher incidence of graft loss than the wild-type (AA) (40% versus 8%; P = 0.006). A study by Lee et al 25 found that the GSTP1 A313G mutant homozygous (AA) allele was associated with increased risk of graft loss ( P = 0.01). Low Bu exposure is thought to be the most common factor influencing graft loss.…”
Section: Discussionmentioning
confidence: 99%